Conceptual Design of Accelerator Driven Subcritical Aqueous Homogeneous Reactor for Isotope Production - LI Huanxing, XIA Zhaodong, LIU Feng, ZHOU Qi, ZHU Qingfu, NING Tong, SUN Xu, KE Guotu (Yuanzineng kexue jishu, 2024)
99Tcm is the most widely used radioisotope in the field of nuclear medicine at present, which is used for clinical diagnosis of diseases and research on the structure and function of organs generally. The existing medical 99Tcm is mainly obtained through the decay of 99Mo generated by irradiating low enriched uranium (LEU) or high enriched uranium (HEU) solid targets in the experimental reactor. There are drawbacks such as complex processes, high costs and long-distance transportation losses. In addition, the global number of medical isotope production reactors is relatively small and most of them were built in the 1950s and 1960s. They face a series of issues such as aging, unstable operation and retirement. The accelerator driven subcritical aqueous homogeneous reactor, which was proposed based on the strengths and weaknesses of producing medical isotopes through accelerators and aqueous homogeneous reactors, has the advantages of high inherent safety, high isotope specific activity and simplified extraction process as a new isotope production technology, making it a research hotspot in recent years. Besides, there is no need to consider the complex and redundant safety protection system in the design, thus the reactor body construction cost is lower and the operation management is more flexible, making it convenient for the simultaneous construction and operation of multiple modular production devices. Based on the basic theory of the subcritical system, this thesis determines the core design principles, explains the accelerator neutron source and fuel selection, completes the conceptual design of the subcritical core by using the Monte-Carlo program, and gives a series of design parameters including keff, neutron flux density and power. The initial design conditions are as follows: The entire subcritical core is approximately a concentric cylindrical structure, with the accelerator neutron source at the center, following the neutron multiplication layer, the uranyl nitrate solution zone, and the water reflection layer unit from inside to outside. In addition, the long-life burnup characteristics of the core and the 99Mo capacity were calculated and analyzed using relevant burnup procedures to demonstrate the feasibility of the plan. The subcritical core scheme has a low power level and is safe and reliable. When the extraction efficiency is 60%, the annual production of 99Mo could reach over 20 kCi, which could meet one-third of the present clinical needs of our country with a conservative estimate. All of the above work has important practical significance for mastering the production technology of 99Mo and achieving engineering applications in the future.